THE MEANING OF PSYCHOLOGICAL EMPOWERMENT IN BUILDING PROFESSIONALISM AMONG MADRASAH EMPLOYEES: A PHENOMENOLOGICAL STUDY AT MAN 1 NGAWI (INTERNATIONAL SEMINAR, 2025)
Psychological empowerment has become a crucial factor in enhancing employee professionalism within public organizations, including faith-based educational institutions. However, the meaning of psychological empowerment is often limited to structural or managerial aspects, while the subjective experiences of employees remain underexplored. This study aims to understand the meaning of psychological empowerment in fostering employee professionalism at Madrasah Aliyah Negeri (MAN) 1 Ngawi . A qualitative phenomenological approach was employed, with data collected through in-depth interviews, participatory observation, and documentation involving ten key informants consisting of teachers, administrative staff, and school leaders. Data analysis followed the stages of reduction, presentation, and interpretation of essential meanings using an interpretative phenomenological model. The findings reveal that psychological empowerment is perceived not solely as organizational trust but as recognition of the spiritual, moral, and social values embedded in employees' professional identity. Professionalism emerges through three core meanings: (1) a sense of ownership and moral responsibility toward the institution, (2) self-efficacy in performing religious and administrative roles, and (3) commitment to service grounded in religious values. This study concludes that psychological empowerment in public madrasah institutions is rooted in the synergy between organizational trust and institutional spirituality. Theoretically, these findings extend the concept of psychological empowerment within the context of religious bureaucracy, while practically, they provide guidance for madrasah leaders in developing a professional work culture based on values and meaningful engagement.